The potential of participatory democracy in the conditions of the information society - Nikitenko , Lilia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article is devoted to clarifying the potential of participatory democracy in the conditions of the information society.It is suggested that the potential of participatory democracy in the conditions of the information society be recognized as a set of opportunities caused by the development of the Internet and digital technologies, the use of which leads to the effective practical implementation of the ideals and values of participatory democracy.It has been proven that participatory democracy has great potential in the information society, which consists in the application of certain digital innovations covering a wide range of new technologies and methods that transform society and bring it to a new progressive level.It was revealed that the potential of participatory democracy is manifested in such digital innovations as electronic voting, artificial intelligence, blockchain, crowdsourcing.It is argued that the use of these digital innovations has a positive effect on the development of participatory democracy through the creation of favorable conditions for civic activity; uniting a large number of citizens around common goals; bringing society closer to the government; reduction of long-term costs of financial, labor and time resources; improving political transparency, control and security. However, each of them has its own challenges and risks, overcoming which requires solving a number of technical, legal and ethical issues.